Impaired Development of Left Anterior Heart Field by Ectopic Retinoic Acid Causes Transposition of the Great Arteries - Mayu Narematsu; Tatsuya Kamimura; Toshiyuki Yamagishi; Mitsuru Fukui; Yuji Nakajima (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2015)
Background Transposition of the great arteries is one of the most commonly diagnosed conotruncal heart defects at birth, but its etiology is largely unknown. The anterior heart field (AHF) that resides in the anterior pharyngeal arches contributes to conotruncal development, during which heart progenitors that originated from the left and right AHF migrate to form distinct conotruncal regions. The aim of this study is to identify abnormal AHF development that causes the morphology of transposition of the great arteries. Methods and Results We placed a retinoic acid–soaked bead on the left or the right or on both sides of the AHF of stage 12 to 14 chick embryos and examined the conotruncal heart defect at stage 34. Transposition of the great arteries was diagnosed at high incidence in embryos for which a retinoic acid–soaked bead had been placed in the left AHF at stage 12. Fluorescent dye tracing showed that AHF exposed to retinoic acid failed to contribute to conotruncus development. FGF8 and Isl1 expression were downregulated in retinoic acid–exposed AHF, and differentiation and expansion of cardiomyocytes were suppressed in cultured AHF in medium supplemented with retinoic acid. Conclusions The left AHF at the early looped heart stage, corresponding to Carnegie stages 10 to 11 (28 to 29 days after fertilization) in human embryos, is the region of the impediment that causes the morphology of transposition of the great arteries.